Financing and Funding Health Care: Optimal Policy and Political Implementability - Robert Nuscheler; Kerstin Roeder (Center for Economic Studies and ifo Institute (CESifo), 2014)
Health care financing and funding are usually analyzed in isolation. This paper combines the corresponding strands of the literature and thereby advances our understanding of the important interaction between them. We investigate the impact of three modes of health care financing, namely, optimal income taxation, proportional income taxation, and insurance premiums, on optimal provider payment and on the political implementability of optimal policies under majority voting. Considering a standard multi-task agency framework we show that optimal health care policies will generally differ across financing regimes when the health authority has redistributive concerns. We show that health care financing also has a bearing on the political implementability of optimal health care policies. Our results demonstrate that an isolated analysis of (optimal) provider payment rests on very strong assumptions regarding both the financing of health care and the redistributive preferences of the health authority.
Keywords: H24; I14; I18; 330; health care financing; provider payment; service quality; cost containment; political economy